2001
DOI: 10.2337/diabetes.50.9.2164
|View full text |Cite
|
Sign up to set email alerts
|

Role of Allelic Variants Gly972Arg of IRS-1 and Gly1057Asp of IRS-2 in Moderate-to-Severe Insulin Resistance of Women With Polycystic Ovary Syndrome

Abstract: To assess the role of insulin receptor, insulin receptor substrate (IRS)-1, and IRS-2 genes in insulin resistance, we explored the genomic DNA in women with polycystic ovary syndrome (PCOS) and a variable degree (mean ؎ SE) of insulin resistance (homeostasis model assessment index for insulin resistance [HOMA IR ] 3.2 ؎ 0.6, n ‫؍‬ 53; control subjects 1.56 ؎ 0.34, n ‫؍‬ 102) using direct sequencing. Whereas no novel mutations were found in these genes, gene-dosage effects were found on fasting insulin for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
78
5
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(101 citation statements)
references
References 24 publications
11
78
5
5
Order By: Relevance
“…Allele frequencies were in Hardy-Weinberg equilibrium in each racial/ethnic group. The frequency of the variant allele was 0.06 for nonHispanic whites and 0.07 for African Americans; these frequencies were similar to the value of 0.07 (range 0.051-0.11) previously described for a general population sample [40].…”
Section: Resultssupporting
confidence: 88%
“…Allele frequencies were in Hardy-Weinberg equilibrium in each racial/ethnic group. The frequency of the variant allele was 0.06 for nonHispanic whites and 0.07 for African Americans; these frequencies were similar to the value of 0.07 (range 0.051-0.11) previously described for a general population sample [40].…”
Section: Resultssupporting
confidence: 88%
“…In Caucasians, Finns, and Chinese, however, this variant was not associated with type 2 diabetes (5,6). Although the polymorphism was associated with decreased insulin sensitivity and impaired glucose tolerance in women with polycystic ovary syndrome (7), it showed no association with insulin sensitivity in other studies (6,8,9). In contrast, another study in women with polycystic ovary syndrome found that homozygous carriers of the Gly1057 allele had higher 2-h plasma glucose concentrations during an oral glucose tolerance test (OGTT) (10).…”
mentioning
confidence: 89%
“…In Caucasians, Finns, and Chinese, however, this variant has not shown an associated with type 2 diabetes [58,59]. Although the polymorphism was associated with decreased insulin sensitivity and impaired glucose tolerance in women with polycystic ovary syndrome [60], it showed no association with insulin sensitivity in other studies [59,61,62]. In contrast, another study in women with polycystic ovary syndrome found that homozygous carriers of the Gly1057 allele had higher 2-h plasma glucose concentrations during an oral glucose tolerance test (OGTT) [63].…”
Section: Mutations Of Irs As a Cause Of Insulin Resistancementioning
confidence: 92%